Airflow patterns and turbulence characteristics above the canopy of a tomato crop in a roof-ventilated insect-proof screenhouse. (February 2020) - Teitel, Meir; Liang, Hao; Vitoshkin, Helena; Tanny, Josef; Ozer, Shay
Abstract : Airflow patterns and turbulence characteristics inside a naturally ventilated screenhouse with tomato plants were experimentally investigated using 3D sonic anemometers simultaneously measuring air velocities at six horizontal positions in the space between the screened roof and the top of the canopy. The screenhouse had a flat roof and was ventilated through the roof only. Testing was carried out during about 3 weeks of crop development, under variable external conditions. The mean horizontal air velocity component above the canopy was generally lower than 0.20 Uoh (where Uoh  is the mean horizontal external wind speed) and mostly in a direction opposite to the external wind. At low external windspeed, the airflow direction was not necessarily opposite to the wind direction. The vertical air velocity component was generally lower than 0.07 Uoh . The root mean square of the air velocity components, the turbulence intensity and the turbulence kinetic energy were much larger during the day than at night mainly due to the higher daytime effect of buoyancy and to a lesser extent due to the higher external wind speed. Spectral energy slopes of the velocity components were close to −5/3 during the day when wind speed was high. However, at night, when wind speed was low, the spectral energy slope of the velocity vector increased significantly. The integral length scales of turbulent eddies were greater in the horizontal than the vertical direction which is not surprising given the volume under consideration is bounded by the top of the canopy, the roof and the sidewalls. Highlights: Flow characteristics above the canopy in an insect-proof screenhouse were studied. Mean horizontal airflow, was generally in a direction opposite to external wind. Inflow and outflow were on leeward and windward screenhouse sides, respectively. Velocity components RMS and TKE gradually increased until noon and then decreased. Slopes of spectral energy density were about −5/3. At low wind speed slopes increased.